Business Process Improvement of Asset Recording in the General Affairs (GA) Division Using the Business Process Improvement (BPI) Method at PT LOLC Ventura Indonesia - Lutfi Cahya Tresnayadi; Jeferson Siahaan; Nino Setyo Utomo (CV ODIS, 2026)
This study aims to analyze and improve the asset recording business process at PT LOLC Ventura Indonesia using the Business Process Improvement (BPI) method developed by Harrington. The background of this study is based on several issues faced by the company, including the asset recording process that has not been fully digitalized, inefficient workflow, and lack of integration among related departments. These conditions result in delays in data updates, difficulties in asset tracking, and potential recording errors, which ultimately affect the company’s operational performance. The BPI method is applied to evaluate the existing business process (as-is process) by mapping the workflow using Business Process Model and Notation (BPMN) and identifying activities categorized as Value Added (VA), Business Value Added (BVA), and Non-Value Added (NVA). Furthermore, a streamlining analysis is conducted to identify non-value-added activities and to design a proposed business process (to-be process) that is more efficient, simplified, and integrated. The improvement focuses on eliminating non-value-added activities, simplifying workflows, and enhancing integration between related functions. The results of this study indicate that the proposed business process improvements significantly enhance operational efficiency. Based on flow analysis, the cycle time decreases from 7.88 days to 5.89 days, representing an efficiency improvement of 25.6%. In addition, the process cost is reduced from IDR 868,494 to IDR 799,744, resulting in a cost efficiency of 7.9%. Simulation results also demonstrate performance improvements, including reductions in minimum time by 30.4%, maximum time by 25%, and average time by 26.9%, along with cost savings of 21.8%. These findings confirm that implementing a more integrated business process through the BPI approach can improve operational efficiency, accuracy in asset recording, and overall asset control within the company.